Emergency Response Services Suicide: A Crisis in Canada?. Issue 7 (3rd October 2017) - Koopmans, Erica; Wagner, Shannon L.; Schmidt, Glen; Harder, Henry
ABSTRACT: This literature review sought to examine the extant literature on the relationship between emergency response services (ERS) personnel and suicide in Canada. The purpose was to determine what research has been conducted on suicide and suicide ideation among ERS, to contribute to knowledge in the area, and also to identify potential research gaps. Through a search of multiple databases (PubMed, Web of Science, Medline, Psyc Articles, Psyc Info, Science Direct, CINAHL) and additional hand searching, 40 articles were identified to meet search criteria and provide relevant information on this topic. The articles revealed that research has primarily focused on the traumatic stress and critical incidents encountered by emergency responders, while little research has been conducted specifically on suicide within these professions. The minimal research that has focused on suicide generally discusses ERS encounters with suicide victims and patients, rather than suicide in the context of their personal mental health. The limited research that does discuss ERS suicide is largely restricted to law enforcement and military personnel. Finally, the literature search identified a particular lack of research relevant to the Canadian context. A research agenda is recommended to further investigate suicide among ERS within Canada, and the impact these suicides have on colleagues, families and friends.